2017
DOI: 10.1017/s1047951116002304
|View full text |Cite
|
Sign up to set email alerts
|

Morbidities in the ultra-athlete and marathoner

Abstract: The cardiovascular benefits of habitual exercise are well documented. In the current era, more of the population is exceeding the recommendations for physical activity as the popularity of endurance events increases. Recent data have proposed a U-shaped relationship between exercise intensity and cardiovascular outcomes. Regular participation in endurance activities has been shown to result in structural and functional changes in the heart. This re-modelling may be the substrate for cardiac dysfunction or arrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…It seems that LV dysfunction and long-term endurance exercise may imply a myocardial injury and were both responsible for an elevated release of the cardiac biomarkers [10,31]. Importantly, echocardiographic and cardiac biomarkers analyses in this study group, obtained after 48 h of completion of the ultra-marathon demonstrated that most of these indices of cardiac function had normalized.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…It seems that LV dysfunction and long-term endurance exercise may imply a myocardial injury and were both responsible for an elevated release of the cardiac biomarkers [10,31]. Importantly, echocardiographic and cardiac biomarkers analyses in this study group, obtained after 48 h of completion of the ultra-marathon demonstrated that most of these indices of cardiac function had normalized.…”
Section: Discussionmentioning
confidence: 75%
“…There has been evidence that hypertrophic cardiomyopathy was a frequent cause of sudden cardiac death among endurance athletes, followed by cardiac anomalies, myocarditis, and arrythmogenic diseases [31]. Nevertheless, research results on ultra-marathon races were controversial and limited to observing the main cardiac biomarkers levels and their association with runners’ age, finish times [20], echocardiography [14], training status [21,32] or altitude variation [33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, sudden cardiac arrest and fetal arrhythmias are often encountered in long-distance runners [ 32 ]. Vigorous or prolonged exercise activity frequently incurs the activation of pathological cardiac pathways and yields elevated biomarkers of cardiac damage [ 33 ]. Furthermore, some competitive long-distance runners developed exercise-induced hypertension, which was associated with an abnormal level of angiotensin-II [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The practice of ultraendurance sports has become increasingly popular in recent years, mostly for recreational athletes [37][38][39]. Additionally, there is extensive evidence that ultraendurance races and regular ultraendurance training may lead to long-term health problems, including cardiovascular, respiratory, musculoskeletal, renal, immunological, gastrointestinal, neurological, and skin problems [40,41]. As ED is characterized by continuous exercise despite significant and interfering physical problems that are likely to have been caused by intense exercising, it is essential to better understand the continuum and psychological and/or interactional mechanisms underlying ED in ultraendurance athletes to prevent both mental health issues and related health problems [42].…”
Section: Introductionmentioning
confidence: 99%